Analysis of Hots-Based Learning Outcomes Assessment Instruments in Class VII Mathematics Learning at MTs At-Taqwa Beru - Roja, Anisa Fatima (EduMatika: Jurnal MIPA, 2023)
Mathematics learning based on the 2013 curriculum aims to develop students' knowledge, understanding, and analysis skills of the natural environment and its surroundings. The assessment of the 2013 curriculum explicitly requested that teachers in schools in balance in conducting assessments in three domains of domains, namely cognitive, affective and psychomotor in accordance with their goals to be measured. One of the abilities that are considered low according to the teacher and most students are the ability to solve mathematical problems that are categorized as HOTS. Through the matter of hots, the curiosity and understanding of students of the material also increase. This research is a type of qualitative research with a qualitative and quantitative descriptive approach. In this study, validity, reliability, problem distinguishing power and difficulty level were conducted. The results showed that the aspect of its validity was that there were 2 (8%) the problem was very significant, 8 (32%) the problem was categorized as significant, and 15 (60%) the category was not significant. Reliability test results on questions belong to the high category. The results of his research show that the results of the analysis of the distinguishing power of the learning outcomes test items are questions that have good differentiating power should be entered and recorded in the bank's book. And the results of the difficulty level of the difficulty have not met the criteria as good, as the level of difficulty is unbalanced.